Evaluating Phytochemical, Antioxidant, Ascorbic Acid Equivalent Capacity and Antimicrobial and Synergistic Effects of Stolon of Colocasia esculenta Against Clinical Pathogens (Dhaka University Journal of Pharmaceutical Sciences, 2026)
Abstract not availableDhaka Univ. J. Pharm. Sci. 25(1): 75-80, 2026 (June)